Influence of HCP/BCC interface orientation on the tribological behavior of Zr/Nb multilayer during nanoscratch: A combined experimental and atomistic study. (1st May 2023) - AlMotasem, A.T.; Daghbouj, N.; Sen, H.S.; Mirzaei, S.; Callisti, M.; Polcar, T.
Abstract: Zr/Nb6 multilayers of 6 nm periodicity, with well-composition-modulated structures, were prepared by magnetron sputtering. Their microstructure and scratch properties were investigated using HAADF-STEM, XRD, AFM, and triboindenter. The Zr/Nb interfaces have various orientations along the growth direction. The hardness (H) and reduced elastic modulus (E) are measured as 6.6 GPa, and 176.3 GPa, respectively, resulting in a high ratio of H/E, compared to other multilayer systems such as Ta/Co and Ag/Cu, which indicates superior tribological performance. The coefficient of friction (COF) was 0.27, and the elastic recovery was observed along the scratch path. Extensive large molecular dynamics simulations (MD) were conducted to investigate the impact of different Zr/Nb interface orientations on the friction/wear behavior of Zr/Nb6 multilayers. The primary cause of plastic deformation of the Nb layer was dislocations and BCC twinning, while Zr layers deform via dislocations and intrinsic stacking faults. The Zr/Nb6 exhibited better tribological properties, such as lower COF, higher scratch hardness, and improved wear resistance compared to their single-crystal counterparts. The Pitsch-Schrader interface showed the lowest COF value, whereas Rong–Dunlop and Zhang-Killy orientations exhibited better wear resistance. The interface structure was analyzed, and its blocking strength was discussed. These findings contribute to understanding the relationship between Zr/Nb interface and wear performance and tailoring them to achieve desired properties for specific applications. Graphical abstract: Image, graphical abstract